KONSISTENSI NAHDLATUL ULAMA’ DALAM MEMPERTAHANKAN PANCASILA DAN KEDAULATAN NEGARA KESATUAN REPUBLIK INDONESIA DI TENGAH WACANA NEGARA ISLAM - Farih, Amin (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2019)
Since its establishment, NU has always prioritized the interests of the nation and state based on Islamic shari'a and Islamic values, Indonesianism and has a high spirit of nationalism. By using qualitative research and historical methods, this article comprehensively describes how NU, as one of the largest CSOs in Indonesia has its own way of placing roles and realizing its contribution in upholding the concept of Pancasila and maintaining the sovereignty of Indonesia in the frame of the Unitary State. Republic of Indonesia (NKRI). The results of this study explain that NU refused to firmly reject the idea of khilafah and the concept of an Islamic State in Indonesia, this attitude has been shown by NU by rejecting the presence of the Indonesian Islamic State (NII) founded by Kartosuwiryo. This attitude of rejection of the concept of khilafah was also indicated by the attitude of NU's (Nahdlatul Ulama?) recognition that decided the position of the Head of State of the Republic of Indonesia (Ir. Sukarno) as w?liy al-amri al-?ar?ri bi al-shawkah or de facto with full power in the NU Ulema Alim National Conference in Cipanas in 1954 and the 20th NU Congress Decision in Surabaya, 8-13 September 1954. The consistency of the attitude pointed out by NU continued in the New Order and until the reform era, now to keep rejecting the khilafah system.